Readiness for Change Scale in Higher Education: Adaptation and Validity of the Indonesia Version - Neka Erlyani; Rahkman Ardi; Fendy Suhariadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The Readiness for Change Questionnaire was created to assess readiness and ability to face new things and change. It is still being determined whether this scale is also relevant in the context of governance changes in higher education, especially in Indonesia. Method: This study examines the scale of cross-cultural adaptation and assesses the modified version using higher education as an organizational context. Translation, synthesis, back-translation, engagement with subject experts, and an emphasis on readability were all part of the thorough scale adaptation process by the International Test Commission (ITC) Guidelines for Translating and Adapting Test. The researchers performed an anonymous self-administered survey and gathered 534 responses from two samples of non-academic staff working in different universities. Results: Results showed that the scale, consisting of 25 questions divided into four subscales, had acceptable fit indices using CFA and excellent internal consistency. Novelty: The findings show that the scale is appropriate for assessing organizational readiness for change and may contribute to research and practical implications for higher education institutions experiencing governance changes.